Dominicus Germanus de Silesia’s Approach to the Qur’an: A first assessment (with critical edition) - Cecini, Ulisse (Studia Islamica, 2024)
Dominicus Germanus de Silesia’s 17th century translation of the Qur’an, Interpretatio Alcorani Literalis, offers a new approach to the long history of Latin translations of the Qur’an. In line with the early modern, humanistic, “philological” trend, he aims to explore the original sources of his object of study. However, he takes this concept further by considering as “source” not only the authentic Qur’anic text, but also the most authoritative Qur’anic commentators, whom he also translates into Latin and incorporates into the translation. This paper is a first attempt to analyze in detail Dominicus’s modus operandi, his sources and how he relates them to the Qur’anic text, as well as the purpose of his work. The study includes the critical edition of sura 9, 28-35 in the Interpretatio Alcorani Literalis, both in the translation and in the commentary parts of the work.